Isolation and Identification of Naphthalene-Degrading Bacteria and its Application in a Two-phase Partitioning Bioreactor - Deng, Ran; Li, Jing; Liu, Bo Yu; Li, Qiang; Du, Jie; Lu, JianGuo; Hou, QianRu (Journal of general and applied microbiology, 2024)
Naphthalene is a persistent environmental pollutant for its potential teratogenic, carcinogenic and mutagenic effects. In this study, 10 strains of bacteria capable of degrading naphthalene were isolated from crude-oil contaminated soil. Among them, Pseudomonas plecoglossicida 2P exhibited prominent growth with 1000 mg/L naphthalene as the sole carbon source and degraded 94.15% of naphthalene in 36 h. Whole genome sequencing analysis showed that P. plecoglossicida 2P had a total of 22 genes related to naphthalene degradation, of which 8 genes were related to the salicylic acid pathway only, 5 genes were related to the phthalic acid pathway only, 8 genes were common in both the salicylic acid and phthalic acid pathways, and 1 gene was related to the gentisic acid pathway. P. plecoglossicida 2P was applied in a two-phase partition bioreactor (TPPB) to degrade naphthalene in wastewater. The optimal operating conditions of the reactor were obtained through response surface optimization: initial naphthalene concentration (C0) =1600 mg/L, bacterial liquid concentration (OD600) = 1.3, and polymer-to-wastewater mass ratio (PWR) = 2%. Under these conditions, the naphthalene degradation rate was 98.36% at 24 h. The degradation kinetics were fitted using the Haldane equation with a high coefficient of determination (R2=0.94). The present study laid foundations for naphthalene degradation mechanism of genus Pseudomonas and its potential application in TPPB.